USE OF SOCIAL MEDIA INSTAGRAM AS A MEDIA PROMOTION OF LIBRARY INFORMATION SERVICE IN MARKETING MANAGEMENT PERSPECTIVE - BAKHTIYAR, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The purpose of medical research is to describe the use of Instagram social media as a means of promoting libraries. Research based on careful analysis based on detailed comprehensive studies with the main discussion of content focusing on the use of Instagram social media in the promotion of library information services.The research includes in-depth analysis studies, always based and focused on major studies on various important reasons for the use of Instagram social media in library promotion activities. Analyzing requires realistic critical thinking to apply a concept, so that it is appropriate to use the historical approach, characterized by a critical realistic investigation of thought development. Primary information sources are the most important component, utilized for primary data.Data collection techniques dominate the utilization of library research, carry out activities to read literature subjected to social media discussion, Instagram, library promotion. The analysis activity is qualitative descriptive analysis, the source of analysis comes from various theoretical readings, research and not research. Research dominates the description, examination and evaluation of factual facts to reach solutions to solve problems in phenomena.Validity can be achieved need to use content analysis, useful to analyze the various meanings of important concepts. Observation of various library promotion activities in his daily life is used to construct theories, especially the meaning of social media instagram and promotion activities of library information services in the era of the industrial revolution 4.0. The results showed; Instagram as a library promotion media has a strategic position and role to promote library information services to the general public. Libraries can convey a variety of information in the form of design, which can attract the attention of users so that the utilization of library information services can be increased and maximized.